PREVALENCE, PERCEIVED CAUSES AND CONSEQUENCES OF PRE-MARITAL SEX AMONG SECONDARY SCHOOL STUDENTS IN EKITI STATE - Olanike Adaramoye, Toyin; Tosin Omotoso, Gift; Olayiwola- Adedoja, Tolulope; Olajumoke Dikko, Basirat; Bamidele Iretor-Oscar, Oluwaseun (African Journal of Social and Behavioural Sciences, 2025)
This study investigated the prevalence, perceived causes, and consequences of pre- marital sex among secondary school students in Ekiti State. The research was conducted in the Oye-Ekiti Local Government Area of Ekiti State. The study population comprised senior secondary school students from government-owned secondary schools within the local government area. A total of 200 students were randomly selected to participate in the study. Data was collected through the administration of questionnaires and analysed using descriptive statistical methods, including frequency counts, percentage distributions, and mean rank order analysis. The findings show that most secondary school students engage in premarital sex, indicating a high prevalence of this behaviour. Further findings also revealed that the causes of premarital sex include pornography, drugs, curiosity, unmet needs, low self-esteem, environmental factors, changes in societal values, financial pressure, experimentation, high libido, alcoholism, peer influence, modernisation, smoking, financial inducements, poverty, self-gratification, and involvement in gang activities. It was also deduced that the consequences of premarital sex, as expressed by secondary school students, include poor academic performance, exposure to HIV/AIDS, loss of respect, abortion, loss of life, exposure to other sexually transmitted infections and diseases, dropping out of school, distractions, unwanted pregnancy, depression, and rejection. It was recommended that comprehensive, age-appropriate sex education be implemented in schools starting in early adolescence, covering not only biological aspects but also relationships, consent, decision-making skills, and the potential consequences of sexual activity.